PERAN WAKAF DALAM PEMBERDAYAAN EKONOMI PEREMPUAN - Rozalinda Rozalinda (Kafa`ah: Journal of Gender Studies, 2012)
Women have an important contribution to the economy. Contribution of women in the micro, small and medium enterprises (SMEs) is quite large. Is a small micro economic activities became the choice of most members of society, particularly women's groups, they are many involve in industrial activities crafts and home industries. Development of waqaf money to acquire a strategically. Endowments money can be invested and distributed to economically empower women entrepreneurs through micro-finance and business assistance. Cash waqaf management institutions to empower women by providing working capital and business development Keywords : Women, Mikro finance, enpowerment, entrepreneurshipCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.40